Arousal, valence, and volume: how the influence of online review characteristics differs with respect to utilitarian and hedonic products. Issue 3 (4th May 2019) - Ren, Jie; Nickerson, Jeffrey V.
ABSTRACT: Online reviews influence consumers' purchase decisions. Product type – specifically, whether a product is utilitarian or hedonic – can help explain how consumers react to reviews. Characteristics of reviews – in particular, valence, measured by ratings, the arousal level of the language used in the text and the volume of the reviews – provide heuristics that consumers may use in making purchase decisions. Product type moderates the effect of these characteristics. Empirical evidence for this claim comes from multiple sources: a panel data analysis of 26, 357 Amazon products and an online experiment with 541 participants. The findings of studies based on this evidence show that product type (hedonic or utilitarian) moderates the effect of the three heuristic attributes of online reviews (valence, volume, and arousal) on sales. The analysis uses OLS-fixed effects models and Granger causality tests. These findings explain why past studies have found that sometimes online review valence is more influential than volume and arousal with respect to sales and why sometimes this is reversed. Our findings have significant theoretical and practical implications for the design of choice architectures in online review systems.